THE INFLUENCE OF ORGANIZATIONAL CULTURE AND SITUATIONAL LEADERSHIP TO EMPLOYEE ENGAGEMENT THROUGH COMPENSATION AS A MEDIATOR AT PT. ASTRA WELAB DIGITAL ARTA - Akbar, Ali; Robinson Manurung, Antonius Dieben (Dinasti Publisher, 2020)
This study aims to determine the influence of organizational culture and situasional leadership on employee engagement through compensation as a mediator. The population in this study were all employees at PT. Astra Welab Digital Arta which has 216 employees. The data analysis technique used is Structural Equation Model (SEM) with Lisrel, sample of this research uses purposive sampling. The results showed that there is a positive and significant influence of organizational culture to compensation, there is a positive and significant influence of situational leadership to compensation, there is a positive and significant influence of organizational culture and situational leadership to compensation, there is a positive and significant influence compensation to situational leadership, there is a positive and significant influence of organizational culture and situational leadership on employee engagement through compensation as a mediator